Non-Myeloablative Allogeneic Transplantation with Post-Transplant Cyclophosphamide after Immune Checkpoint Inhibition for Classic Hodgkin Lymphoma: a Retrospective Cohort Study - Paul, Suman (Biol Blood Marrow Transplant, 2020)
BACKGROUND: Immune checkpoint inhibitors (ICIs) are approved in relapsed classic Hodgkin lymphoma (cHL). The safety and effectiveness of allogeneic blood or marrow transplantation (alloBMT) in ICI pretreated cHL patients remain unclear. The aim of this study is to assess outcomes of cHL patients receiving ICIs before alloBMT using post-transplantation cyclophosphamide (PTCy) graft-versus-host-disease (GVHD) prophylaxis. METHODS: We performed a retrospective study of relapsed/refractory cHL patients undergoing alloBMT with PTCy at Johns Hopkins between Nov 2004 and Sept 2019. Engraftment, GVHD incidence, nonrelapse mortality (NRM), progression free survival (PFS) and overall survival (OS) were compared between patients receiving pre-alloBMT ICI or standard salvage chemotherapy. FINDINGS: We identified 105 consecutive relapsed/refractory cHL patients, of which 37 (35.2%) received ICIs and 68 (64.7%) received chemotherapy without ICIs (no-ICI) before alloBMT. ICI and no-ICI patients experienced a 3-year estimated OS of 94% versus 78%, [hazard ratio (HR) 0.35 (95% CI: 0.081.56), P=0.17) and a 3-year estimated PFS of 90% and 65% [HR 0.3 (95 % CI: 0.09–1), P=0.05], respectively. We observed no statically significant difference in the 12-month cumulative incidence of acute grade II-IV GVHD or in the 24-month incidence of chronic GVHD. INTERPRETATION: ICIs do not increase acute or chronic GVHD incidence compared to salvage chemotherapy. cHL patients receiving ICIs prior to alloBMT experienced outstanding PFS and OS. Thus ICI therapy is safe in cHL patients when undergoing alloBMT with PTCy and may improve post-alloBMT disease progression and survival.